PENGARUH LATIHAN DRILLING SERVIS FOREHAND PANJANG BULUTANGKIS TERHADAP AKURASI PUKULAN - Alamsyah, Shoffan; Sudarmanto, Eko (Universitas Hamzanwadi, 2025)
This study aims to examine the effect of badminton long forehand serve drilling training. This research method is experimental. This study used a one group pretest-posttest design. The population in this study was 50 students. The technique of determining the sample using purposive sampling as many as 20 students. The instruments used are generally forehand service technique tests. Data analysis techniques using descriptive statistical analysis and inferential analysis. Based on the results of the pretest normality test data obtained with a value of 0.908 > 0.05 and posttest data with a value of 0.082 > 0.05, the data is normally distributed. Homogeneous test for pretest and posttest data is 0.153 which means > 0.05 the data is homogeneous. Data from the hypothesis test used to compare the pretest results of 5.950 and posttest 13.50 with a significant value of 0.000 was also obtained. Therefore the pretest result is 5.950 > posttest 13.50 and a significant value of 0.000 < 0.05. From the data analysis, description, testing of research results, and discussions that have been carried out, it can be concluded that this study is a long forehand service drilling exercise has a significant effect on increasing the accuracy of badminton shots on students of Universitas Muhammadiyah Surakarta.